Criminality-oriented terrorist learning: an interactive model - Eser, Ercan (2016)
This thesis, focusing on the reasons beyond immediate terrorist and criminal events, studies ‘how’ and ‘why’ terrorist organizations (TOs) and organized crime groups (OCGs) act, react and evolve. It adopts a ‘criminality oriented approach’ that puts discrete pieces of terrorism under a microscopic examination and explains terrorist learning of criminality: how tacit knowledge required for terror tactics and organized crime is processed and saved in the secret domains of TOs and OCGs and how the knowledge is accessed and learned by other illegal organizations. Using Akers’ social learning theory, it explains that TOs and OCGs influence each other through a hybrid network structure and they learn non-traditional activities that require knowledge, skills and techniques (organized crime for TOs and terrorism for OCGs) through associations. It also argues that the associations among them result in the appropriation of tactics and modus operandi, and that the closer association of the two groups may cause the mutation of both organizations. It develops a dynamic model that explains the relationship between terrorism and organized crime and the mutative behaviours of TOs and OCGs. Depicting the present and future capabilities of TOs and OCGs and possible future forms of both terrorism and organized crime threats, it offers pathways to prevent TOs from learning and to strengthen counterterrorism measures.